Pertanggungjawaban Pidana Terhadap Pelaku Pencabulan Anak Di Bawa Umur - Hammi Farid; Ifahda Pratama Hapsari; Hardian Iskandar (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
Children are a gift given by God Almighty, which we must protect and take care of because every child also has the right to live.  The rise of cases of sexual harassment by adults against minors both in the school environment and in the public environment shows the lack of protection for children, and causes physical and psychological impacts that are directly felt by children as victims of sexual abuse.  Sexual harassment of minors must be addressed with real action, and prevented as early as possible.  Prevention can be done through sex education, not only from parents but also from other parties including schools.  Protection measures. Children must be started as early as possible, so that later they can participate optimally for the development of the nation and the State, for that someone who commits his actions must be held accountable and punished according to what was done